ANALISIS PENGGUNAAN E-FILING BERDASARKAN KEMUDAHAN DAN MINAT PERILAKU WAJIB PAJAK ORANG PRIBADI - Hani Sri Mulyani; Dadang Sudirno; Nadya Purnamasari (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2023)
The use of e-filing that occurred from 2016-2020 continues to increase, this is becauseSPT reporting using e-filing can speed up and save resources that must be spent.However, there are still obstacles for taxpayers including taxpayers still havingdifficulty using e-filing and taxpayers feeling e-filing is difficult to access because noteveryone can access e-filing due to unsupported networks. This study aims to examinethe effect of convenience and interest on the behavior of individual taxpayers on the useof e-filing on individual taxpayers at KP2KP Majalengka. The research population isindividual taxpayers at KP2KP Majalengka who have a normal/valid NPWP.Determination of the research sample by non-probability sampling that is purposivesampling based on several criteria. The research sample is 100 respondents. The testsinclude validity and reliability tests. This data analysis technique includes classicalassumption test, multiple linear regression analysis, coefficient of determinationanalysis, hypothesis testing with t test and F test. The results of the study show thatconvenience and behavioral interest partially affect the use of e-filing significantly.